Towards Making a Green City: A Case Study of Ilam Municipality - Poudel, Pratik; Hong, Shao Ying (Bodhi: An Interdisciplinary Journal, 2013)
This article reports a brief household survey done in every ward of Ilam municipality about the statuses of various prerequisites of a green city. The surveyer found out that the general household has only little knowledge about the concept of a green city. Similarly, chemical fertilizer was least used, which is a good sign. Many households still have traditional cooking stove which emits more smokes. Almost all households surveyed had a well-equipped sanitational facility. Many households complained that they were not receiving adequate drinking water. Even in the irrigation part, there were not enough irrigation sources DOI: http://dx.doi.org/10.3126/bodhi.v6i0.9244 Bodhi Vol.6 2013: 36-49